Developing Supply Chain Management and Lean Environment for Improving the Company Performance - Svetlana A. Kucheryavenko; Svetlana A. Gayvoronskaya; Dmitry A. Popov; Irina V. Chistnikova (International Journal of Supply Chain Management, 2019)
Abstract- The article discusses the ways to improve the efficiency of enterprises and organizations in a constantly changing and competitive environment. They analyzed the approaches to the definition of "lean production". They clarified the concept of â€œproduction systemsâ€ for regional economic entities. They analyzed the factors limiting the effective implementation of lean production tools in enterprises and organizations. Based on the analysis and comparison of approaches to the definition of â€œinnovation environmentâ€ notion, the author suggests the approach of the â€œlean environmentâ€ development in the region.